2018
DOI: 10.4172/1948-5964.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti-retroviral Therapy among HIV Positive Pregnant Women in Ayder Refferal Hospital, Northern Ethiopia

Abstract: Background: Human Immunodeficiency Virus (HIV) is one of the major global public health problems. Antiretroviral therapy (ART) helps to prevent transmission of HIV from infected pregnant women to the un-born babies. ART adherence rate, as high as 95% is crucial to effectively decrease maternal viral load and risk of vertical transmission of HIV. The aim of this study was to evaluate ART adherence level among HIV positive pregnant women in Ayder referral hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…15,18,20 Studies conducted in Ethiopia reported that adherence to Option B plus ART ranged from 81.1% to 95.1%. 15,[21][22][23][24][25][26] Moreover, our study is similar to a study conducted in Malawi (72%). 22 On the other hand, low adherence was reported among pregnant and lactating women (52.1%) and lactating women (44.9 and 51%) in Uganda.…”
Section: Discussionsupporting
confidence: 84%
“…15,18,20 Studies conducted in Ethiopia reported that adherence to Option B plus ART ranged from 81.1% to 95.1%. 15,[21][22][23][24][25][26] Moreover, our study is similar to a study conducted in Malawi (72%). 22 On the other hand, low adherence was reported among pregnant and lactating women (52.1%) and lactating women (44.9 and 51%) in Uganda.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, ART adherence of at least 95% of the drugs taken at prescribed dosing intervals optimises outcome and minimises occurrence of viral resistance. [19] The adherence prevalence rate found among the HIV-positive pregnant women involved in this study was 73.5% (the pill count method) and this is comparable to the finding reported from south-east Nigeria by Igwegbe et al [6] However, this rate is higher than figures reported from south-west Nigeria and south Nigeria by Olowookere et al [10] and Omonaiye et al [20] respectively, but lower than those reported from Ethiopia by Shibabaw et al [15] and Zambia by Ng'ambi et al [21] The variation in the prevalence rate reported from these studies might be due to differences in the population of the respondents, as well as awareness and practice of PMTCT in the study areas, which were similarly expressed by Ekama et al [13] and Ng'ambi et al [21] Education and occupation of women, partner disclosure of HIV status, having treatment support and use of ARV drugs for PMTCT were the determinants of good medication adherence in this study. A higher level of education was found to be associated with increased likelihood of good medication adherence.…”
Section: Discussionsupporting
confidence: 79%
“…Fear of stigmatisation, discrimination, forgetfulness, feeling of good health, living far away from the hospital and lack of access to transportation, pill burden and side-effects of the drugs were some of the factors found to be associated with suboptimal adherence. [6,[13][14][15] There has been no study in Ekiti State on adherence to ARV medication among HIV-positive pregnant women. Therefore, this study was conducted to determine adherence to ART and the associated factors among HIV-positive pregnant women attending antenatal clinics in Ado-Ekiti, south-western Nigeria.…”
mentioning
confidence: 99%
“…through Medical Stores Limited [7]. With this intervention, the Country had recorded 87 percent increment in the number of infected pregnant and postpartum women initiated into care compared with other previous years [8].…”
Section: Introductionmentioning
confidence: 99%
“…The number of infants who were born from these women and tested HIV positive was reportedly high despite their mothers ever been initiated on cART. Statistics showed that from January to December 2018, 775 HIV exposed infants were tested using Early Infant Diagnosis (EID) testing protocols, 43 of them were positive with HIV Deoxyribo-Nucleic Acid (DNA) [8]. The figure represented a six percent infant positivity rate which was higher compared with the acceptable level of two percent or less as a national standard [10].…”
Section: Introductionmentioning
confidence: 99%